An assessment of the girl child participation in science subjects at advanced level with the introduction of the stem initiative: a case study of Glen View suburb schools. - Marume, Weston (Midlands State University, 2017)
The development discourse has proved beyond doubt that there is no development that we can talk about if it is still discriminating or marginalizing some groups of the society especially women and the girl child. Because of this, this document seeks to assess and analyze the extent to which the girl child is participating in science subjects at advanced level in Zimbabwe concentrating on the period starting 2016 when the STEM Initiative was introduced as a measure to promote a science-based economy and industrialization. It looks into similar situations from other nations that have also implemented the STEM Initiative, and make comparisons and distinctions from them. Case studies of Glen View 1 High and Glen View 2 High Schools from Glen View-Mufakose District of Harare Metropolitan Province were used in the research. Data was collected, Causes of the disparities were uncovered through interviews, questionnaires and observations and at the end conclusions and recommendations were made. This was all done in a bid to try and expose barriers to complete girl child emancipation through science education as well as to put forward measures that will help to encourage them to participate in science subjects, a step towards gender equality and national development inclusive of the girl-child.